The challenge of Mediterranean sclerophyllous vegetation under climate change: From acclimation to adaptation - Bussotti, Filippo; Ferrini, Francesco; Pollastrini, Martina; Fini, Alessio (Environmental and Experimental Botany, 2014)
Forecasting models for climate change in southern Europe differ from those proposed for central and northern regions mainly with regard to precipitation. In fact, a strong reduction in average rainfall, mainly caused by decrease frequency of rainy events, is believe to occur in the Mediterranean basin in the forthcoming hundred years. Increased frequency of drought events will be paralleled and exacerbated by warming. Differently from areas where plant growth is limited by sub-optimal temperature (i.e. boreal and most temperate forests) and where warming has been reported to increase carbon assimilation and growth, plants growing in the Mediterranean basin are currently near their temperature optimum, and warming may contribute (e.g. with drought) to impair photosynthesis and depress growth and survival. Rising atmospheric CO2 has been found to increase growth, photosynthesis water use efficiency, and may partially alleviate the deleterious effects of warming and drought. However, in areas where severe and prolonged drought episodes occur, severe photoinhibition and metabolic limitation to photosynthesis may prevent Mediterranean sclerophylls to take advantage of higher atmospheric CO2, and may slow down recovery after the end of the dry season. The most sensitive forest types consist in tree species which are, in the Mediterranean basin, at the southernmost limit of their distribution range. In contrast, thermophilous trees are expected to have a greater diffusion both in southern and central Europe, as winter cold stress will be reduced by warming. Yet due to great variability of ecological features, the alleged substitution of tree species can follow a natural pattern from south to north and from low to high altitudes, without considering obstacles deriving from urbanization. For these reasons, research on the performance and ecologic plasticity of different genotypes, on species selection, and on planting and management techniques can have strategic importance for adaptive forest management.
Keywords: Drought stress; Global warming; Ozone; photosynthesis; UV radiation; Vegetation shift

Non-invasive tools to estimate stress-induced changes in photosynthetic performance in plants inhabiting Mediterranean areas - Guidi, Lucia; Calatayud, Angeles (Environmental and Experimental Botany, 2013)
In Mediterranean areas, plants are concomitantly exposed to various abiotic stresses such as light intensity, water deficit, extremes in air temperature, air pollutants, etc. These environmental pressures adversely affect plant development. Changes in photosystem activity are an early response of plants to abiotic stresses. Therefore, chlorophyll (Chl) fluorescence and gas exchange, two non-invasive, rapid and inexpensive techniques for measuring photosynthesis in leaves, have been widely used by plant ecophysiologists to analyse plant responses to stressful conditions. Chl a fluorescence and gas exchange parameters can be indeed used to evaluate changes in photochemical and non-photochemical processes in photosystems associated with electron transport, CO2 fixation, and heat dissipation. In this review, we focus our analysis on the effects of different abiotic stresses on the photochemistry of Mediterranean plants using Chl a fluorescence and gas exchange measurements. Since changes in photosynthetic parameters are observed in the absence of visual injuries, these methodologies constitute fundamental tools to predict and evaluate the extent to which abiotic stresses damage photosynthesis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Abiotic stress; Chlorophyll a fluorescence; climate change; Gas exchange; Oxidative stress; photosynthesis

Responses of evergreen and deciduous Quercus species to enhanced ozone levels. - Calatayud, Vicent; Cerveró, Júlia; Calvo, Esperanza; García-Breijo, Francisco-José; Reig-Armiñana, José; Sanz, María José (Environmental pollution (Barking, Essex : 1987), 2011)
Plants of one evergreen oak (Quercus ilex) and three deciduous oaks (Q. faginea, with small leaves; Q. pyrenaica and Q. robur, with large leaves) were exposed both to filtered air and to enhanced ozone levels in Open-Top Chambers. Q. faginea and Q. pyrenaica were studied for the first time. Based on visible injury, gas exchange, chlorophyll content and biomass responses, Q. pyrenaica was the most sensitive species, and Q. ilex was the most tolerant, followed by Q. faginea. Functional leaf traits of the species were related to differences in sensitivity, while accumulated ozone flux via stomata (POD1.6) partly contributed to the observed differences. For risk assessment of Mediterranean vegetation, the diversity of responses detected in this study should be taken into account, applying appropriate critical levels.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 20974507
Keywords: Anatomy; Critical levels; Functional leaf traits; Ozone; photosynthesis; Stomatal conductance

The importance of mesophyll conductance in regulating forest ecosystem productivity during drought periods - KEENAN, Trevor; Sabaté, Santi; Gracia, Carlos (Global Change Biology, 2010)
Water availability is the most limiting factor to global plant productivity, yet photosynthetic responses to seasonal drought cycles are poorly understood, with conflicting reports on which limiting process is the most important during drought. We address the problem using a model-data synthesis approach to look at canopy level fluxes, integrating twenty years of half hour data gathered by the FLUXNET network across six Mediterranean sites. The measured canopy level, water and carbon fluxes were used, together with an inverse canopy ecophysiological model, to estimate the bulk canopy conductance, bulk mesophyll conductance, and the canopy scale carbon pools in both the intercellular spaces and at the site of carboxylation in the chloroplasts. Thus the roles of stomatal and mesophyll conductance in the regulation of internal carbon pools and photosynthesis could be separated. A quantitative limitation analysis allowed for the relative seasonal responses of stomatal, mesophyll, and biochemical limitations to be gauged. The concentration of carbon in the chloroplast was shown to be a potentially more reliable estimator of assimilation rates than the intercellular carbon concentration. Both stomatal conductance limitations and mesophyll conductance limitations were observed to regulate the response of photosynthesis to water stress in each of the six species studied. The results suggest that mesophyll conductance could bridge the gap between conflicting reports on plant responses to soil water stress, and that the inclusion of mesophyll conductance in biosphere–atmosphere transfer models may improve their performance, in particular their ability to accurately capture the response of terrestrial vegetation productivity to drought.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 16 june 2009; conductance limitations; Drought; FLUXNET; june 2009 and accepted; Mediterranean climate; mesophyll conduc-; mesophyll conductance; photosynthesis; received 12 march 2009; revised version received 2; tance; water stress

Why do large, nitrogen rich seedlings better resist stressful transplanting conditions? A physiological analysis in two functionally contrasting Mediterranean forest species - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Jacobs, Douglass F.; Rey Benayas, José M. (Forest Ecology and Management, 2010)
We analysed the physiological bases that explain why large and high nitrogen (N) concentration seedlings frequently have improved survival and growth relative to small seedlings in Mediterranean woodland plantations. Large seedlings of Aleppo pine (Pinus halepensisMill.) and holm oak (Quercus ilex L.) with high N concentration (L+), and small seedlings with either high (S+) or low (S−) N concentration, were planted on two sites of different weed competition intensity that created contrasting stress conditions. Seedling survival, growth, gas exchange, N remobilization (NR) and uptake (NU), and water potential were assessed through the ﬁrst growing season. Weeds reduced survival and growth, but seedling response to weed competition varied among phenotypes and between species. At the end of the ﬁrst growing season, L+ Aleppo pine seedlings had higher survival than both small seedling types in presence of weeds but no differences were observed in absence of weeds. Mortality differences among phenotypes occurred in spring but not in summer. L+ Aleppo pines grew more than small Aleppo pines independently of weed competition. No holm oak seedling type survived in presence of weeds and no mortality differences among phenotypes where observed in absence of weeds, although L+ holm oak seedlings grew more than small seedlings. Mortality and growth differences in Aleppo pine were linked to marked physiological differences among phenotypes while physiological differences were small among holm oak phenotypes. L+ Aleppo pines had greater root growth, gas exchange, NR, and NU than small seedlings, irrespective of their N concentration. Seedling size in Aleppo pine had a greater role in the performance of transplanted seedlings than N concentration. The functional differences among oak phenotypes were small whereas they were large in pine seedlings, which led to smaller differences in transplanting performance in holm oak than in pine. This suggests that the nursery seedling quality improvement for planting in dry sites could depend on the species-speciﬁc phenotypic plasticity and functional strategy. Improved transplanting performance in large Aleppo pine seedlings relative to small seedlings was linked to greater gas exchange, root growth and N cycling.
Keywords: competition; Nitrogen remobilization; photosynthesis; Pinus halepensis; Quercus ilex; Root growth; Stomatal conductance; Survival; water potential

THE INFLUENCE OF FERTILISATION ON SALT (SODIUM CHLORIDE) DAMAGE IN TRANSPLANTED SCOTS PINE (PINUS SYLVESTRIS) AND EVERGREEN OAK (QUERCUS ILEX) - Beis, Vassilios K.; Percival, Glynn C. (Arboricultural Journal, 2009)
Summary The aim of this study was to determine the influence of a range of commercially available fertilisers on tree responses following salt (sodium chloride) damage to foliar tissue of containerized evergreen oak (Quercus ilex) and Scots pine (Pinus sylvestris). Evergreen oak proved to be more salt tolerant than Scots pine. Tree responses to fertilisation following 6% foliar salt spray were measured by chlorophyll fluorescence, photosynthetic rates, leaf chlorophyll content, leaf necrosis and leaf sodium and chloride concentrations over a nine week period. Tree responses were 20?300% higher in fertilised compared to nonfertilised trees, irrespective of species. In all cases non-fertilised trees had the least capacity to respond positively following salt damage. In addition leaf area, shoot, root, total plant dry weight was higher in fertilised trees compared to non-fertilised ones at the end of a nineweek period. Results of this investigation indicate applications of commercially available fertilisers would be of benefit to induce positive tree response rates and subsequent growth following sodium chloride damage to foliar tissue. Selection of an appropriate fertiliser, however, is important as effects on growth and vitality varied widely depending on the type of fertiliser applied.
doi: 10.1080/03071375.2009.9747582doi: 10.1080/03071375.2009.9747582The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: chlorophyll fluorescence; Chlorophylls; photosynthesis; physiogenic stress; plant health care; stress tolerance

The influence of leaf water content and isoprenoids on flammability of some Mediterranean woody species - De Lillis, Manuela; Bianco, Pietro Massimiliano; Loreto, Francesco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2009)
The impact of water content and isoprenoids on leaf flammability was studied. Field and laboratory experiments were carried out on monoterpene-emitting evergreen broad-leaved species (Quercus ilex, Quercus suber); a needle-leaved species (Pinus halepensis) that emits and stores monoterpenes; an evergreen species (Myrtus communis) that emits isoprene but stores monoterpenes; and a deciduous species (Quercus pubescens) that emits isoprene. Photosynthesis, leaf water content (LWC) and isoprenoid emission were measured. Isoprenoid content was calculated. Temperatures of visible smoke, incandescence and flame appearance were recorded. The LWC significantly correlated with both photosynthesis and isoprenoid emissions. Linear correlation and factorial analysis revealed a positive correlation between temperature of flame appearance and LWC and a negative relationship between temperature of flame appearance and isoprenoid emission. Multiple regression analysis indicated that the temperature of flame appearance was reduced in broadleaved monoterpene-emitting species. In monoterpene emitters, the temperature of flame appearance depended for similar to 65% on LWC, whereas monoterpene emissions explained similar to 35% of the dependency. P. halepensis and M. communis, storing high levels of isoprenoids, ignited at high humidity. The results may be explained if isoprenoids indeed facilitate leaf ignition but, being dissolved in water, isoprenoids are also an indicator of a high water content that decreases flammability.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: fire; flammability phases; Monoterpenes; photosynthesis

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - FARIA, T.; Vaz, M.; Schwanz, P.; PolIe, A. (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

Stomatal uptake and stomatal deposition of ozone in isoprene and monoterpene emitting plants - Fares, S.; Loreto, F.; Kleist, E.; Wildt, J. (Plant Biology, 2008)
Volatile isoprenoids were reported to protect plants against ozone. To understand whether this could be the result of a direct scavenging of ozone by these molecules, the stomatal and non-stomatal uptake of ozone was estimated in plants emitting isoprene or monoterpenes. Ozone uptake by holm oak (Quercus ilex, a monoterpene emitter) and black poplar (Populus nigra, an isoprene emitter) was studied in whole plant enclosures (continuously stirred tank reactors, CSTR). The ozone uptake by plants was estimated measuring ozone concentration at the inlet and outlet of the reactors, after correcting for the uptake of the enclosure materials. Destruction of ozone at the cuticle or at the plant stems was found to be negligible compared to the ozone uptake through the stomata. For both plant species, a relationship between stomatal conductance and ozone uptake was found. For the poplar, the measured ozone losses were explained by the uptake of ozone through the stomata only, and ozone destruction by gas phase reactions with isoprene was negligible. For the oak, gas phase reactions of ozone with the monoterpenes emitted by the plants contributed significantly to ozone destruction. This was confirmed by two different experiments showing a) that in cases of high stomatal conductance but under low CO2 concentration, a reduction of monoterpene emission was still associated with reduced O3 uptake; and b) that ozone losses due to the gas phase reactions only can be measured when using the exhaust from a plant chamber to determine the gas phase reactivity in an empty reaction chamber. Monoterpenes can therefore relevantly scavenge ozone at leaf level contributing to protection against ozone.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: isoprene; Monoterpenes; Ozone uptake; photosynthesis; reaction chambers; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 - Aranda, Xavier; Agustí, Cristina; Joffre, Richard; Fleck, Isabel (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2; Elevated CO2; Fluorescence (voyant); Growth; photosynthesis; Resprouts

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Effects of the interaction between drought and shade on water relations, gas exchange and morphological traits in cork oak (Quercus suber L.) seedlings - Aranda, I.; Castro, L.; Pardos, M.; Gil, L.; Pardos, J. a (Forest Ecology and Management, 2005)
The combined effect of drought and light on different physiological and biochemical traits was assessed in cork oak (Quercus suber L.) seedlings grown under two levels of light availability and submitted to a long-standing drought. Watering was withdrawn after germination and seedlings were allowed to dry to a water content of ca. 50% of ﬁeld capacity. At this point, water-stressed seedlings were grown under moderate drought and two light regimes: high light (HL—50%) and low light (LL— 2%). Soil water in control plants was kept close to ﬁeld capacity (90–100%) for both light environments. Water-relations parameters derived from P–V curves, gas exchange and water status at predawn (Cpd ) were evaluated at twice during the experiment. Nitrogen and chlorophyll contents were determined in the same leaves used for the gas exchange measurements. In addition, maximum rate of carboxylation (Vcmax) and electronic transport (Jmax) were derived from A–Ci curves in well-watered seedlings. The variation on moisture availability during the experiment was the same under both light environments. In control plants, Cpd was over 0.3 MPa at the two harvests, while stressed seedlings decreased to 0.9 MPa, with no differences between light treatments. Water stress decreased osmotic potentials at full (Cp100 ) and zero turgor (Cp0 ). The regressions between both potentials and Cpd showed a higher intercept in shade grown seedlings. This fact will point out the higher osmoregulation capacity in sun seedlings whatever water availability. Nitrogen investment on a per leaf mass (Nmass ), chlorophyll content (Chlmass ) and SLA tended to show a typical pattern of sun-shade acclimation. Thus, the three parameters increased with shade. Only for Nmass there was a signiﬁcant effect of watering, since water stress increased Nmass . LL plants showed a lower photosynthetic capacity in terms of maximum net photosynthesis at saturating light (Amax), which was related to a decrease in Vcmax and Jmax . Both parameters varied with speciﬁc leaf area (SLA) in a similar way. The low-light environment brought about a higher nitrogen investment in chlorophyll, while under high-light environment the investment was higher in carboxylation (Vcmax) and electronic transport ( Fmax). Stomatal conductance to water vapour (gwv ) and Amax were lower in low-light seedlings independently of watering. In addition, there was a trend to keep higher intrinsic water use efﬁciency (IWUE) under high light environment. The increase of IWUE under water stress was higher in HL seedlings. This was as consequence of the steeper decline in gwv as Cpd decreased. The decrease of Amax with Cpd occurred in a similar way in LL and HL seedlings. Thus, the HL seedlings tended to sustain a higher ability to increase IWUE than LL seedlings when they were submitted to the same water stress.
Keywords: Cork oak; Drought; light; osmotic adjustment; photosynthesis; water use efficiency

SEASONAL PATTERN OF PHYSIOLOGICAL STATE IN A CORK OAK (QUERCUS SUBER L.) STAND IN HUELVA (SPAIN) - GONZÁLEZ-PÉREZ, ARANTZAZU; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL; FERNÁNDEZ, MANUEL (Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005., 2005)
The seasonal pattern of the physiological state of Quercus suber is determined by different ecological factors, and it affects to the growth of the species. The main objective of this study is to know the seasonal pattern of water potential, photosynthesis and fluorescence in four Quercus suber L. trees and to relate these values with ecological factors during two years. In this time there were three critical periods, the first one the end of the dry period where the water potential descends to values less than -3MPa and the photosynthesis to 0.781 µmol CO2m-2 s-1Quercus suber, physiology, water potential, photosynthesis, fluorescence. . The second critical period is located in period of change of the leaf, between the months of March and May. The third critical period occurred due to the freezes and drought of the year 2005, that produced strong damages in the PSII.
The following values have no corresponding Zotero field: periodical: Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005. pub-location: Huelva
Keywords: fluorescenc; photosynthesis; physiology; Quercus suber; water potential

Direct and indirect impacts of fire on isoprenoid emissions from Mediterranean vegetation - Alessio, G. A.; Lillis, M. De; Fanelli, M. (Functional Ecology, 2004)
1. Fire is often associated with episodes of air pollution, possibly involving the release of biogenic isoprenoids (isoprene and monoterpenes). The direct and indirect impacts of ﬁre on isoprenoid emission by plants of the Mediterranean vegetation were studied. Leaves of Arbutus unedo, Phillyrea latifolia, Cistus incanus, Cistus mospeliensis, Pistacia lentiscus, Quercus ilex, Quercus suber, Quercus pubescens, Myrtus communis and Pinus halepensis were exposed to direct ﬁre or to the ﬁre-consequent wave of elevated temperature. 2. Half the tested plant species did not emit isoprenoids and the treatments did not induce isoprenoid emission. In contrast, isoprene was emitted by intact leaves of Q. pubescens and M. communis, while monoterpenes were emitted by intact leaves of Q. ilex, Q. suber and P. halepensis. 3. The two treatments rapidly reduced isoprene emission by isoprene-emitting species and monoterpene emission by Quercus spp. This inhibition was associated with photosynthetic inhibition, and recovery was seen in Quercus spp. within days of treatment. Recovery was also associated with the recovery of photosynthesis, suggesting that emitted isoprenoids continue to be formed predominantly from photosynthetic intermediates after a ﬁre episode. 4. In Q. pubescens leaves, however, recovery from the elevated-temperature treatment caused a sustained increase of isoprene emission which was not mirrored by a similar increase in photosynthesis. Whether this represents the induction of alternative metabolic pathways or an increase of the ﬂux of photosynthetic carbon in the isoprene pathway is not known. Isoprene-emitting species in areas surrounding ﬁre may emit a substantially larger hydrocarbon ﬂux for several days after ﬁre. 5. The elevated-temperature treatment induced the emission of α-pinene from Myrtus leaves, and the ﬁre treatment stimulated the emission of several monoterpenes from Pinus needles. The emission began to decrease within minutes in Myrtus, while it increased within the ﬁrst 100 min in Pinus, where it was detectable the day after the event although the ﬂux was smaller than in prestressed needles. 6. Exposure to ﬁre and to the associated elevated temperature may induce bursts of monoterpenes from plants that regularly do not emit these compounds and temporarily increase the load of monoterpenes in the atmosphere by pine species. These emissions may contribute to photochemical reactions involved in smog and ozone formation
Keywords: isoprene; Mediterranean plant species; Monoterpenes; Ozone; photosynthesis; Stomatal conductance; ﬁre ecology

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Radiocarbon as a biomarker of urban pollution in leaves of evergreen species sampled in Rome and in rural areas (Lazio—Central Italy) - Alessio, M.; Anselmi, S.; Conforto, L.; Improta, S.; Manes, F.; Manfra, L. (Atmospheric Environment, 2002)
The aim of the present study is the use of 14 C, sampled in leaves of evergreen species, as a natural geochemical marker to estimate the contribution of artiﬁcial sources (heating plants, vehicles, etc.) to the complex of atmospheric gases in an urban environment. Leaves were chosen due to sampling easiness and their reliability: in particular the evergreen species, being exposed all the year round to pollutants are especially indicated for bioindication and biomonitoring studies. The response to atmospheric pollutants has been studied of two plant species (Quercus ilex L., Pinus pinea L.) measuring isotopic ( 14 r, d 13 C), chemical (Pb concentration) and ecophysiological (gaseous exchange and leaf ﬂuorescence of chlorophyll a) parameters. Leaves of holm-oaks and stone pine needles collected over a 3-year time span in an urban park in Rome (Villa Ada) and in reference localities outside the city on the Tyrrhenian coast and in the preAppennine area have been analysed. In Villa Ada measurements were carried out along a transect from the road bordering the park towards the interior; all the parameters, together in agreement, showed a decreasing pollution gradient towards the inner park. It was possible to estimate a 5.570.3% contribution of CO2 from fossil fuels close to the road, decreasing to 1.770.3% at o300 m from it towards the inner park. The isotopic analyses conducted on stone pines and holm-oaks show that 14 C provides indications on the degree of pollution from fossil fuels, while d 13 C appears to be conditioned mainly by the interspeciﬁc difference, and also by many other environmental factors that affect the plant functionality. Results conﬁrmed that radiocarbon is a useful tool in environmental studies, allowing to quantify the contributions of CO2 of anthropic origin: this parameter, together with appropriate isotopic, chemicaland ecophysiological analyses, could provide a good indication of the ‘‘air quality’’ in urban and rural contexts.
Keywords: air quality; carbon isotopes; co 2; lead; photosynthesis

Estado hídrico y demanda de fotosintesis de Quercus ilex, Quercus faginea y Pinus halepensis MICORRIZADOS ARTIFICIALMENTE CON Tuber melanosporum EN VIVERO - DOMÍNGUEZ, J. A.; R. PLANELLES; RODRÍGUEZ BARREAL, J. A.; SAÍZ DE OMEÑACA, J. A.; ZAZO, J.; TEYSSIERE, M.; MARTINEZ, G.; PINAZO, O. (III Congreso Forestal Español Congreso, 2001)
We have been carried out a periodic control in Quercus ilex, Quercus faginea and Pinus halepensis inoculated with Tuber melanosporum Vitt. during the first year of growth in nursery with a water-non stressed régime; in all the species, the minimum water potential and transpiration rate didn't reflect any differences for the treatment, but in some cases, the photosynthesis rate was major in inoculated seedlings. K.W.:
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: ectomycorrhiza; photosynthesis; Pinus halepensis; Quercus faginea; Quercus ilex; Tuber

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L.; Schulte, M.; Raschi, A.; Slee, N.; Rennenberg, H.; Polle, A. (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco

Fumigation with exogenous monoterpenes of a non-isoprenoid-emitting oak (Quercus suber): monoterpene acquisition, translocation, and effect on the photosynthetic properties at high temperatures - Delfine, Sebastiano; Csiky, Olav; Seufert, Guenther; Loreto, Francesco (New Phytologist, 2000)
We tested if fumigation with exogenous monoterpenes might induce thermotolerance in leaves of an oak species (Quercus suber) which does not form and emit isoprenoids. To understand if exogenous monoterpene fumigation results in internal accumulation of monoterpenes, a physical method of monoterpene extraction was used. The internal content of monoterpenes increased in concert with increasing fumigation doses. This unambiguously demonstrated acquisition of exogenous monoterpenes. We exposed fumigated Q. suber leaves to two cycles of increasing temperatures from 35 to 55°C at 5°C steps. When leaves were exposed to a low dose of exogenous monoterpenes, yielding an internal content similar to that endogenously formed in the leaves of the monoterpene- emitter Q. ilex, no clear improvement in thermotolerance was found. When leaves were exposed to a high dose of exogenous monoterpenes, yielding an internal content of about ®ve fold the endogenous pool of Q. ilex, but comparable with the expected content following stress-induced stomatal closure, photosynthesis inhibition at high temperatures was attenuated. This eﬀect was observed only at temperatures !45°C during the ®rst cycle, but at all temperatures between 35 and 55°C when plants were exposed to two cycles of high temperatures. Monoterpenes were still found in the leaves of Q. suber 12 h after ending the fumigation. Monoterpenes were also found in non-fumigated leaves distant up to 45 cm from the fumigated leaves. If monoterpenes make the photosynthetic apparatus more resistant to high temperatures, the eﬀect might not be limited to the fumigated leaves and might be persistent after fumigation.
Keywords: isoprenoid emission; Monoterpenes; photosynthesis; Quercus suber; thermotolerance

On the monoterpene emission under heat stress and on the increased thermotolerance of leaves of Quercus ilex L. fumigated with selected monoterpenes - Loreto, F.; Förster, A.; Dürr, M.; Csiky, O.; Seufert, G. (Plant, Cell & Environment, 1998)
Leaves of the monoterpene emitter Quercus ilex were exposed to a temperature ramp with 5 °C steps from 30 to 55 °C while maintained under conditions in which endogenous emission of monoterpenes was allowed or suppressed, or under fumigation with selected exogenous monoterpenes. Fumigation with monoterpenes reduced the decline of photosynthesis, photorespiration and monoterpene emission found in non-fumigated leaves exposed to high temperatures. It also substantially increased respiration when photosynthesis and photorespiration were inhibited by low O2 and CO2-free air. These results indicate that, as previously reported for isoprene, monoterpenes may help plants cope with heat stress. Monoterpenes may enhance membrane stability, thus providing a rather non-specific protection of photosynthetic and respiratory processes. Monoterpene emission was maximal at a temperature of 35 °C and was inhibited at higher temperatures. This is likely to be the result of the temperature dependency of the enzymes involved in monoterpene synthesis. In contrast to other monoterpenes, cis- and trans-β-ocimene did not respond to exposure to high temperatures. Cis-β-ocimene also did not respond to low O2 or to fumigation. These results indicate that cis and trans-β-ocimene may have a different pathway of formation that probably does not involve enzymatic synthesis.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: monoterpene emission; monoterpene fumigation; photosynthesis; Quercus ilex; respiration; thermotolerance

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology